Cross sectional study of knowledge and practices regarding breast feeding amongst mothers belonging to tribal community in Melghat area, Amravati, Maharashtra, India - Chavan, Sushil; Jadhao, Ashok; Narlwar, Uday; Ughade, Suresh; Adikane, Hemant (International Journal of Research in Medical Sciences, 2017)
Background: Delayed breastfeeding initiation, colostrum deprivation, supplementary feeding of breast milk substitutes, early introduction of complementary feeding, and incorrect weaning from breast milk are commonly found practices in tribal communities around the world. Aim of the study was to assess the breast-feeding knowledge and practices among mothers belonging to tribal community and having children less than 1 years of age in Melghat area, Maharashtra, India. Methods: Present cross-sectional study was conducted in 14 villages of 4 sub centres of Bijudhawadi, Primary Health Centre in Dharni block of Amravati District, Maharashtra, India. Mothers belonging to tribal community having child less than one year and Mothers who were permanent residents of study area were included in study. Interview was planned as per the convenient time of the mother. Finally, 225 study subjects could be contacted during study period. Results: The mean age of mothers was 22.47 years with SD 3.24 years with range 16 - 35 years. Majority 178 (79.11%) study subjects were having correct knowledge about initiation of breastfeeding. Correct practice of initiation of breastfeeding within 1 hour was seen in 167 (74.22%) study subjects. Significant difference was seen among correct knowledge and practice Colostrum initiation, Pre-lacteals, Period of exclusive breastfeeding. Conclusions: The present study was an attempt to understand knowledge and practices regarding breastfeeding in the context of tribal mothers in Melghat, Maharashtra, India.